HOW DOES THE STUDENTS’ CRITICAL THINKING ABILITY IN GEOMETRY OPTICS? - Sutrisno, Fery Hadi; Handayanto, Supriyono Koes; Supriyana, Edi; Laksmisari, Rusna (Unnes Science Education Journal, 2018)
One of the abilities that must be possessed by students in the 21st century is the ability to think critically. This article aims to analyze students' critical thinking skills in geometric optical materials. This research is descriptive research with subject of research consisted 116 student grade 12 SMA. The critical thinking skills test instrument consists of 12 items about the description of geometric optical material with reliability coefficient of 0.701. The results of this study indicate that the average ability of critical thinking students 14.54 of scale 100 with the highest score of 48 and the lowest value 1.3. This shows that students' critical thinking skills are still in the low category. The weakest aspect of critical thinking ability is argument analysis. Need efforts to improve students' critical thinking skills, one of them is by applying learning that requires students actively in solving problems.